The effects of post warm-up recovery time on jumping performance / Ainun Ajeerah Abd. Halim - Abd. Halim, Ainun Ajeerah (2021)
A warm up is a routine for an athlete doing before start the training and competition. The body physiologically has potential to improve performance and the effectiveness of warm-up on performance influenced by warm-up intensity, duration and the recovery time between warm-up and the event. However, there is restricted evidence of recovery time on jumping performance. The aim of this study was to investigate the effects of post warm-up recovery time on jump performance. This study is a repeated-measures study design consists of different recovery time as exposures. Fifteen male trained athletes were recruited. Participants exposed to five exposures, no rest, 5 minutes of recovery time (5RT), 10 minutes of recovery time (10 RT), 15 minutes of recovery time (15 RT), 20minutes of recovery time (20 RT) of post warm-up. Participants performed a general warm-up of 10-15 minutes jogging at self-pace and five exercise of dynamic stretching before undergo the recovery time exposure and proceed to countermovement jump .Participants underwent 72 hours recovery period before the next exposure. Participants completed the exposure in a randomized order. The data was analyzed by using one-way ANOVA with repeated-measures. As results, 5RT (15.75%) had significantly improved jump performance (p≤ 0.000) when compared to control. The jumping performance of no rest and 10RT were significantly slower compared to 5RT with 13.97% (p≤ 0.000) and11.29% (p≤ 0.000). The possible reason 5RT is suitable to improve sprint performance might due to shorter period that helped in maintain an elevated core temperature compare to longer rest period. In conclusion, the present study found that 5 minutes of post warmup recovery time is the most effective recovery time for jump performance.